Optimizing Photosensitizer Delivery for Effective Photodynamic Inactivation of Klebsiella pneumoniae Under Lung Surfactant Conditions - Fernanda Alves; Isabelle Almeida de Lima; Lorraine Gabriele Fiuza; Zoe A. Arnaut; Natalia Mayumi Inada; Vanderlei Salvador Bagnato (Pathogens)
Klebsiella pneumoniae is a Gram-negative, encapsulated bacterium recognized by the World Health Organization (WHO) as a critical priority for new therapeutic strategies due to its increasing multidrug resistance (MDR). Antimicrobial photodynamic therapy (aPDT) has emerged as a promising alternative to antibiotics, exhibiting a broad spectrum of action and multiple molecular targets, and has been proposed for the treatment of clinically relevant infections such as pneumonia. However, despite excellent in vitro photodynamic inactivation outcomes, the success of in vivo therapy still faces challenges, particularly due to the presence of lung surfactant (LS) in the alveoli. LS entraps photosensitizers, preventing these molecules from reaching microbial targets. This study investigated the potential of indocyanine green (ICG) in combination with the biocompatible polymer Gantrez™ AN-139 for the photoinactivation of K. pneumoniae. Initial in vitro experiments demonstrated that aPDT with ICG alone is effective against K. pneumoniae in a concentration- and light dose-dependent manner, achieving total eradication at 75 µg/mL of ICG and 150 J/cm2 of 808 nm light. When aPDT was performed with similar parameters in the presence of LS, no bacterial killing was observed. However, a significant synergistic effect was observed when ICG (25 µg/mL) was combined with a low concentration of Gantrez™ AN-139 (0.5% m/v) in the presence of dipalmitoylphosphatidylcholine (DPPC), the main component of LS. This formulation resulted in a substantial reduction (3.6 log10) in K. pneumoniae viability. These findings highlight the potential of Gantrez™ AN-139 as an efficient carrier to enhance the efficacy of ICG-mediated aPDT against K. pneumoniae, even in the presence of lung surfactant, a necessary step before the in vivo experiments.